Effect of cell cycle position on thermotolerance in Saccharomyces cerevisiae. - Plesset, J (1987)
We showed that the heat killing curve for exponentially growing Saccharomyces cerevisiae was biphasic. This suggests two populations of cells with different thermal killing characteristics. When exponentially growing cells separated into cell cycle-specific fractions via centrifugal elutriation were heat shocked, the fractions enriched in small unbudded cells showed greater resistance to heat killing than did other cell cycle fractions. Cells arrested as unbudded cells fell into two groups on the basis of thermotolerance. Sulfur-starved cells and the temperature-sensitive mutants cdc25, cdc33, and cdc35 arrested as unbudded cells were in a thermotolerant state. Alpha-factor-treated cells arrested in a thermosensitive state, as did the temperature-sensitive mutant cdc36 when grown at the restrictive temperature. cdc7, which arrested at the G1-S boundary, arrested in a thermosensitive state. Our results suggest that there is a subpopulation of unbudded cells in exponentially growing cultures that is in G0 and not in G1 and that some but not all methods which cause arrest as unbudded cells lead to arrest in G0 as opposed to G1. It has been shown previously that yeast cells acquire thermotolerance to a subsequent challenge at an otherwise lethal temperature during a preincubation at 36 degrees C. We showed that this acquisition of thermotolerance was corrected temporally with a transient increase in the percentage of unbudded cells during the preincubation at 36 degrees C. The results suggest a relationship between the heat shock phenomenon and the cell cycle in S. cerevisiae and relate thermotolerance to transient as well as to more prolonged residence in the G0 state.